To the Islands – Photographs of Tropical Colonies in The Queenslander - Perkins, Hannah (History compass, 2010)
Australian readers knew a great deal about the Pacific Islands in the early 20th century. This understanding came from missionary fund-raising campaigns, visiting lantern-slide lecturers, postcards and illustrated books and encyclopaedia but most of all, after the mid-1890s, from heavily illustrated weekend newspapers. These were published in all major cities and offered a regular visual window on ‘the islands’, of which three were Australian colonies shortly after World War I. This paper argues that Australians were well-informed about the potential for settlement, and commercial and economic opportunities. It notes that illustrated newspapers were dominated by ethnographic images of the material culture and lifestyles of island peoples, but that images of wharves, plantations, port towns and colonial infrastructure were provided for those readers who thought the western Pacific should become an Australian or at least a British sphere of interest. Ultimately The Queenslander’s editorial motivation was to alert Australian readers to the economic potential of plantations, trade, mining, travel and settling in the nearby tropics.